Bank Compliance, Asset Quality, Liquidity to the Financial Sector Profitability Sub Sector Bank Listed on the Indonesia Stock Exchange Period 2018-2020 - Aldi Samara; Metta Susanti; Rina Sulistiyowati; Ida Adhani (Komunitas Dosen Indonesia, 2022)
What motivates researchers to conduct this research is the Lowest Credit to Store Proportion of Banks Since 2016 (M. Richard., 2020) and Policy Strategy Facing the Pandemic: Maintaining Liquidity (Feni Freycinetia, 2020). This journal aims to analyze and test and analyze Bank Compliance, Asset Quality, Liquidity to Profitability either partially or simultaneously. The population in this journal is the financial sector of the banking sub-sector listed on the Indonesia Stock Exchange (IDX) for the 2018-2020 period as many as 43 companies. With the sample in this journal as many as 27 companies that match the criteria of the companies that are sampled in this study. The type of research in this journal is causative quantitative research. sources, the information used in this journal is secondary information. The information that will be used in this journal is in the form of annual reports of sub-sector bank companies listed on the Indonesia Stock Exchange for the 2018-2020 period . The results of hypothesis testing in this journal show the effect of Bank Compliance, Asset Quality, Liquidity on Profitability simultaneously at 0.421 which can be concluded that the Bank Compliance, Asset Quality, Liquidity variables are simultaneously able to explain the Profitability variable of 42.1%. Is stated that the rate of return of the modular, assets, assets, (current loans, bad loans) affect profitability substantially. The rest is influenced by factors other than this journal. And the results of paris research in this journal can be percentaged, namely the influence of Liquidity is the most dominant influence among other variables with a percentage level of 30.2427% while the Asset Quality variable is only able to affect the Profitability variable of 7.31%, and the influence of Bank Compliance is 4 ,5715%